Identification of mitochondrial carrier homolog 2 as an important therapeutic target of castration-resistant prostate cancer - Yankui Liu; Anjie Chen; Yufan Wu; Jiang Ni; Rong Wang; Yong Mao; Ning Sun; Yuanyuan Mi (Cell Death and Disease)
Abstract We here investigate the expression of the mitochondrial carrier homolog 2 (MTCH2) and its potential function in castration-resistant prostate cancer (CRPC). Bioinformatic analyses reveal that MTCH2 overexpression is associated with critical clinical parameters of prostate cancer. Single-cell sequencing data indicate elevated MTCH2 expression in the prostate cancer epithelium. MTCH2 is also upregulated in locally treated CRPC tissue and various primary human CRPC cells. Using genetic silencing via shRNA and knockout (KO) through the CRISPR-sgRNA approach, we showed that the depletion of MTCH2 impaired mitochondrial function, resulting in a reduced oxygen consumption rate, diminished complex I activity, and decreased ATP levels, mitochondrial depolarization, and increased reactive oxygen species production in primary CRPC cells. The silencing or KO of MTCH2 significantly inhibited cell viability, proliferation, and migration, together with a marked increase in apoptosis in the primary CRPC cells. In contrast, ectopic expression of MTCH2 provided CRPC cells with pro-tumorigenic properties, enhancing ATP production and promoting cell proliferation and migration. MTCH2 silencing also markedly inhibited the growth of subcutaneous xenografts of the primary CRPC cells in nude mice. The MTCH2-silenced xenografts exhibited increased apoptosis, elevated lipid peroxidation, and decreased ATP levels. These results provide new insights into the role of MTCH2 in supporting mitochondrial function and CRPC progression.